The church of women: gendered encounters between Maasai and missionaries - Hodgson, Dorothy L. (Indiana Univ. Press, 2005)
"Oh she who brings the rain" -- Men of the church -- Evangelizing "the Maasai" -- The church of women -- Being a man in the church of women -- Possessed by the Spirit -- Toward a Maasai Catholicism?